How Digital Technology Enhances Hotel Experience? Examining Experiential Marketing of Two Four-Star Hotels in Yogyakarta - Patrick, Maryness; Paulo, William Msilu; Sumarwan, Antonius (E-Journal of Tourism; Volume 10 Number 1 (March 2023)DO - 10.24922/eot.v10i1.98359, 2023)
This study intends to understand how digital technology in particular digital marketing and e-commerce enhance hotel experience. There are few studies discussing how these aspects of technology enhances hotel experience through adoption of the sensory elements of experiential marketing. This is a qualitative study conducted through observation and authors’ individual experience of digital and e-commerce channels of the two four-star hotels in Yogyakarta. Content analysis was used to draw conclusion about the data obtained from observation, individual experience and electronic media of professional publications. The results suggest that stimulating and enhancing hotel experience with digital marketing and e-commerce was inseparable with involving the sensory elements. Moreover, the two hotels not only optimized the sensory elements, but also presented these elements interestingly, creatively, uniquely and thoughtfully. Those sensory elements were designed to communicate, persuade and impact users of the hotels whilst observing consistency and clear purpose. This study extends the hotel sector digital and experiential marketing literature. Moreover, the study’s results assist hotel service providers in understanding the importance of involving experiential aspects in their marketing. Thus, the paper relieves hotel managers for more added values especially in marketing plans. However, this study focuses exclusively on four-star hotels in Yogyakarta Region in Indonesia.